Role of the Extracellular Matrix in Alzheimer’s Disease - Sun, Yahan; Xu, Sen; Jiang, Ming; Liu, Xia; Yang, Liang; Bai, Zhantao; Yang, Qinghu (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is a neurodegenerative disease with complex pathological characteristics, whose etiology and pathogenesis are still unclear. Over the past few decades, the role of the extracellular matrix (ECM) has gained importance in neurodegenerative disease. In this review, we describe the role of the ECM in AD, focusing on the aspects of synaptic transmission, amyloid-β-plaque generation and degradation, Tau-protein production, oxidative-stress response, and inflammatory response. The function of ECM in the pathological process of AD will inform future research on the etiology and pathogenesis of AD.